Adsorption of light green and brilliant yellow anionic dyes using amino functionalized magnetic silica (Fe3O4@SiO2@NH2) nanocomposite. Issue 9 (2nd September 2019) - Erdem, Beyhan; Avşar, Saliha Büşra; Erdem, Sezer; Tekin, Nalan
Abstract: Fe3 O4 @SiO2 @NH2 nanocomposite was prepared for highly effective adsorption of two anionic dyes one of which is triarylmethane dye (light green, LG) and the other is azo dye (brilliant yellow, BY). The characterization results demonstrated that superparamagnetic Fe3 O4 nanoparticles were covered with silica and functionalized with amino groups successfully without losing magnetic character. The effects of adsorbent dosage, contact time, pH, temperature, and dye molecular structure on the adsorption were investigated. Acidic pH was better for both LG and BY, on the other hand, alkaline pH was favorable to some extent for LG in comparison with BY due to the contribution of stacking effect in addition to electrostatic attraction. Kinetic data demonstrated that the driving force for adsorption process could be explained by pseudo-second order mechanism in both systems. The equilibrium data were more compatible with Langmuir isotherm than those of Freundlich isotherm and the maximum adsorption capacities of Fe3 O4 @SiO2 @NH2 calculated from Langmuir isotherm model for LG and BY at 30 °C and natural pH of the solution were 40.2 and 35.5 mg g −1 . Thermodynamic calculations related to temperature dependence demonstrated that the adsorption process was spontaneous and exothermic. Graphical Abstract: